Trans-European transport networks and regional economic development - Carsten Schürmann; Klaus Spiekermann; Michael Wegener (European Regional Science Association (ERSA), 2002)
The important role of transport infrastructure for regional development is one of the fundamental principles of regional economics. In its most simplified form it implies that regions with better access to locations of input materials and markets will, ceteris paribus, be more productive, more competitive and hence more successful than more remote and isolated regions. The paper presents results of the research project 'Socio-Economic and Spatial Impacts of Trans-European Transport Networks (SASI)' undertaken for the European Commission. The main goals of the project were to design an interactive and transparent modelling system for forecasting the impacts of transport infrastructure investments and transport system improvements, in particular of the trans-European transport networks (TETN), on socio-economic activities and developments in Europe, including spatial and temporal distribution, and to demonstrate the usability of the modelling system by applying it to a number of relevant case studies. The paper will first explain the theoretical foundation and internal structure of the simulation model developed as well as its input and output. The model is a recursive simulation model of regional socio-economic development subject to exogenous assumptions about the economic and demographic development of the EU as a whole and about transport infrastructure investments and improvements. The second part of the paper will present the results of the application of the model to a set of different assumptions on TETN infrastructure investments and their likely socio-economic impacts on the European regions in terms of GDP per capita, unemployment and accessibility. The model results suggest that the development trajectories of all regions are rather similar in all scenarios, thus confirming the assumption that general socio-economic and technical macro trends are more powerful driving forces for regional economies than infrastructure improvements. It is also shown that some infrastructure scenarios lead to a slightly less polarised distribution of accessibility and GDP among regions, however, not enough to reverse the general trend towards economic polarisation within the European Union. The third part of the paper will outline model improvements currently made in the follow-up project 'Integrated Appraisal of Spatial Economic and Network Effects of Transport Investments and Policies' (IASON). The new model will be more comprehensive in theory and more disaggregate in terms of regions and economic sectors and will include the future member states of the European Union in eastern Europe.
Keywords: 330